Improvement of Management Activities of Private Partnership of Housing: Problems and Solutions - Tonkix Olga Viktorovna (Zien Journals, 2023)
The article examines the nature and significance of the fundamental reforms in the sphere of housing and communal services of the Republic of Uzbekistan. Main goal of this paper work is studying current issues in this area and explaining modern development tendencies regarding public private partnership of housing system in Uzbekistan. Main outcomes of the research are optimization of the regulation and legislation instruments based on the Presidential Decree and some practical suggestions and recommendations for effective problem solving management activities of private homeowners ’partnerships in housing maintenance in Uzbekistan
Keywords: accommodation; housing management; repair and maintenance